Penerapan Metode Krapyak dalam Pembelajaran Saraf di Pesantren - Safitri, Eka (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2017)
Abstract: The research is effort to look how to study saraf with book of krapyak method. The writer do this research with field research is collect information with direct research from place of research. As for kind of research is descriptif research that purpose to explore of condition or etc and then analysis the result of research and expalained in the report of research. Researcher give illustration about the reality of object researched as objective. The research to bring closer on the one variabel about study of saraf  krapyak method. The kind of research method are interview methode, observation and documentation. Latter is analysis fact to get result of research. The result of research adduce that study of saraf in Islamic School Class 2 of Pesantren Mahasiswa (PESMA) An Najah  Purwokerto use eclectic method is integration methods of study saraf in Islamic Studies Class 2 Pesantren Mahasiswa (PESMA) An Najah Purwokerto such as reading method, memorize, demonstratation, dictatation, quetion and answer, discussion, drill and sorogan. This method make student easier for understand about saraf and avoid the students from boredom. Therefore eclectic method right for saraf  learning. Keywords: Pembelajaran saraf, metode krapyak